Educação de Jovens e Adultos: as facetas da evasão na EJA 1ª e 2ª etapa da EMEF “Castelinho do Pequeno Príncipe, do Bairro Vila Nova, no município de Novo Repartimento/PA - HORA, Adilson da Silva da (2021)
This study that is subject to the theme "Education of young and adult: the facets of evasion in the EJA 1st and 2nd stage of the EMEF Castelinho of the small Prince, of the Vila Nova district, in the municipality of New Reparting/PA" has as main objective, investigate the main Factors that lead to the high rate of evasion in the education of young people and adults of the aforementioned school. Thus, in order to achieve this objective, a bibliographical research was carried out through the material already elaborated, consisting of books, scientific articles, resolutions, relevant legislation and publications, with the aim of obtaining Concrete information on the thematic presented. After that, a field survey was carried out, whose subjects were 20 (twenty) students of EJA – 1st and 2nd stage, 2 (two) teachers of this teaching modality and the principal of the school. For the collection of data, a questionnaire consisted of 10 (ten) closed questions, which was applied to students, as well as, through 2 (two) interviews with open questions, one was made up of 5 (five) questions, applied to Teachers, and the other constituted of four (four) questions, directed to the Director of the field of research. The results showed that there are many factors that have contributed directly to the high rate of school dropouts of EJA, from the "Castelinho of the Little Prince" School, among which, the need for most students to have to Work and not have time to study, learning difficulties, lack of public policies for this modality of education, the lack of teachers with specific training to work with young people and adults, the lack of projects that could be Developed and executed by the school, aiming to increase the interest and, consequently, the effective participation of the students, from the beginning to the end of the school year.